Development of executive function and attention in preterm children: A systematic review - Mulder, H.; Pitchford, N.; Hagger, Martin; Marlow, N. (Psychology Press, 2009)
We report on a systematic review of studies of executive function and attention in preterm children. Using meta-analysis, we confirm this is an area of weakness for preterm children, and show that the extent of difficulties is influenced by gestational age (GA), age at test, and skill under investigation. Effect size for selective and sustained attention and inhibition is related to GA. For studies with mean GA 26 weeks, selective attention skills catch up with age, phonemic fluency skills are increasingly delayed, and ongoing deviance is shown for shifting skills (when assessed with specific measures). Implications for research and practice are discussed.